If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8h + 3(4h + -6) = 0 Reorder the terms: 8h + 3(-6 + 4h) = 0 8h + (-6 * 3 + 4h * 3) = 0 8h + (-18 + 12h) = 0 Reorder the terms: -18 + 8h + 12h = 0 Combine like terms: 8h + 12h = 20h -18 + 20h = 0 Solving -18 + 20h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 20h = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 20h = 0 + 18 20h = 0 + 18 Combine like terms: 0 + 18 = 18 20h = 18 Divide each side by '20'. h = 0.9 Simplifying h = 0.9
| -1thirds=7 | | 7x+15=512x | | (-2n^3+8n^2+6)+(4n^3-7n^2)= | | -14x^2-50x+24= | | -2x+2x-5=-5 | | 12-21z= | | A+3a=12 | | 21/2+x+18=306 | | 10y=5x-6 | | -1/4+8= | | 3x(x+1)=12 | | 9d-28=4d-3 | | 9x-x^2=6 | | 8=5-7p^2+10p | | -2x+8=6-2X | | x*-3x-10=0 | | x+8=6-2x | | 3x-2y+3z=-4 | | (4n^3-4n)+(3n^3+7n+8)= | | 2x-y+z=-1 | | 17=-2*x+3 | | 3(7z-4)= | | 25k^2+30k+9=0 | | 125*5-25+10= | | (-3b^2-7b-4)+(7b^2+2b-4)= | | 4t+5+4t-7t=6+2 | | x^2(x^4+16)-8x=0 | | -5=5x^2-25x+25 | | log(6)(5x-3)=4 | | 25+2t=5(t+10) | | 8m+m=14+5m | | 7x+6x-4x=16+2 |